Uji Aktivitas Antibakteri Ekstrak Etanol Daun Jambu Biji Variates Australia (Psidium Guajava Variates Pyrifera) Terhadap Bakteri Escherichia Coli ATCC 25922 Dengan Metode Difusi Dan Dilusi - Fevi Indri Oktaviani; Desy Ayu Irma Permatasari; Danang Raharjo (Lembaga Pengembangan Kinerja Dosen, 2023)
Diarrhea is a disease characterized by frequent bowel movements with watery or watery stool conditions. Symptoms are infections in the intestinal tract due to bacteria, viruses, or other parasitic microorganisms. Not a few cases of diarrhea caused by Escherichia coli bacteria. Plants that can be used as antibacterial one of them is guava leaves variates Australia. Has biological activity as an antibacterial, because it contains several active compounds, such as: tannins, terpenoids, alkaloids, flavonoids, and essential oils. The purpose of this study was to determine the active compounds contained in guava leaves of Australian variates and their antibacterial activity. The extraction method used is maceration with 70% ethanol solvent. Testing its antibacterial activity with the disc diffusion method to see the inhibition zone, then testing the KHM value with liquid diffusion and testing the KBM value with solid diffusion. The results showed that guava leaf extract of Australian variates has antibacterial activity against Eschericia coli ATCC 25922 bacteria. The average diameter of the inhibitory zone in Australian guava leaf extract concentrations of 25%, 12.5%, 6.25%, 3.125%, 1.562%, respectively was 6.6 mm, 3.3 mm, 2.6 mm, 0.83 mm, 1.33 mm. The KHM and KBM values of the liquid dilution test and solid dilution of Australian guava leaf extract in this study were expressed at a concentration of 12.5%.